2019
DOI: 10.1101/553859
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parkin-mediated ubiquitination contributes to the constitutive turnover of mitochondrial fission factor (Mff)

Abstract: The mitochondrial outer membrane protein Mitochondrial Fission Factor (Mff) plays a key role in both physiological and pathological fission. It is well established that in stressed or functionally impaired mitochondria the PINK1 recruits the ubiquitin ligase Parkin which ubiquitinates Mff to facilitate the removal of defective mitochondria and maintain the integrity mitochondrial network. Here we show that, in addition to this clearance pathway, Parkin also ubiquitinates Mff in a PINK1-dependent manner under b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Interestingly, the level of Mff, localized in the mitochondrial outer membrane, decreased in skeletal muscle following 14 days of overload. Lee et al (2019) demonstrated that Mff was ubiquitinated by Parkin; we also confirmed that the expression level of Parkin decreased in the hypertrophied plantaris muscle. This suggests that hypertrophic stimulation promotes the ubiquitination of Mff for turnover by Parkin.…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, the level of Mff, localized in the mitochondrial outer membrane, decreased in skeletal muscle following 14 days of overload. Lee et al (2019) demonstrated that Mff was ubiquitinated by Parkin; we also confirmed that the expression level of Parkin decreased in the hypertrophied plantaris muscle. This suggests that hypertrophic stimulation promotes the ubiquitination of Mff for turnover by Parkin.…”
Section: Discussionsupporting
confidence: 86%
“…Parkin-mediated MFF ubiquitination in response to mitochondrial depolarisation recruits the autophagy adaptor p62, which subsequently facilitates the clearance of damaged mitochondria [ 174 ]. Parkin is responsible for a significant amount of MFF ubiquitination, regulating its constitutive turnover [ 175 ]; however, there is evidence that at least one other ubiquitin ligase targets MFF [ 175 ]. Similar to Mfn1, MFF is also poly-ubiquitinated by atypical chains [ 175 ], indicative of a non-degradative function.…”
Section: Regulating the Fission Machinery By Post-translational Modifmentioning
confidence: 99%
“…Parkin is responsible for a significant amount of MFF ubiquitination, regulating its constitutive turnover [ 175 ]; however, there is evidence that at least one other ubiquitin ligase targets MFF [ 175 ]. Similar to Mfn1, MFF is also poly-ubiquitinated by atypical chains [ 175 ], indicative of a non-degradative function. However, the function of these atypical chains remains to be investigated.…”
Section: Regulating the Fission Machinery By Post-translational Modifmentioning
confidence: 99%
See 1 more Smart Citation